A stochastic simulation approach to estimating the economic impacts of climate change in Bangladesh - Thurlow, James; Dorosh, Paul A.; Yu, Winston (Wiley, 2012)
Climate change assessments often inadequately address uncertainty when estimating damages. Using a dynamic economy‐wide model of Bangladesh, damages from historical climate variability and future anthropogenic climate change are estimated and decomposed. The stochastic simulation approach used avoids biases caused by non‐linear damage functions and fixed occurrences of extreme events in historical data. Using 10 climate projections, it is found that future anthropogenic climate change damages until 2050 are, on average, one‐fifth of those from historical climate variability. Climate change also alters the temporal distribution of damages and slows Bangladesh's long run shift (adaptation) into dry (winter) season rice production.